Frommer's dollarwise guide to the Southeast and New Orleans - Poole, Susan (Susan Winifred) (New York : Frommer/Pasmantier Publishers, 1988)
Includes guides to Virginia, North & South Carolina, Georgia, Florida & the Gulf Coast to New Orleans.
Description based on: 1982-1983 ed.
Latest issue consulted: 1988-1989 ed.
SERBIB/SERLOC merged record
Keywords: Southern States -- Guidebooks; Gulf States -- Guidebooks; New Orleans (La.) -- Guidebooks